Pengaruh Kepuasan Kerja, Lingkungan Kerja dan Disiplin kerja Terhadap Kinerja Karyawan Non-medis Rumah Sakit Muhammadiyah Palembang - Kurnia, Meri; Idris, M; Puspasari, Mardiana (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2025)
This study aims to determine the Influence of Job Satisfaction, Work Environment and Work Discipline on the Performance of Non-Medical Employees of Muhammadiyah Hospital Palembang simultaneously and partially. The type of research uses Associative research, the population is 197 non-medical employees and a sample of 133 employees taken by the Proposive Sampling method. The data used are primary and secondary data. The analysis technique uses multiple linear regression, Hypothesis Test F and t and the coefficient of determination. The results of the study from multiple linear regression that Job Satisfaction, Work Environment and Work Discipline have a positive effect on the Performance of Non-medical Employees of Muhammadiyah Hospital Palembang. The results of the hypothesis test show that there is a significant influence of Job Satisfaction, Work Environment and Work Discipline on the Performance of Non-medical Employees of Muhammadiyah Hospital Palembang, partially there is a significant influence of Job Satisfaction on the Performance of Non-medical Employees, there is a significant influence of the Work Environment on the Performance of Non-medical Employees and there is a significant influence of Work Discipline on the Performance of Non-medical Employees. The results of the determination coefficient show that the variables of Job Satisfaction, Work Environment and Work Discipline are able to explain the rise and fall of Non-Medical Employee Performance by 88.6% while the rest is influenced by other factors outside the study.